Taking CarE of Your Self (Caring & Empathy Cyber Counseling) - Malelak, Erly O.; Loban, Maria N.; Masi, Lolang M.; Boimau, Mes (COUNS-EDU: The International Journal of Counseling and Education, 2023)
Counseling can not only be carried out in person or face-to-face but can also be carried out online. Online counseling can make it easier for every user to get counseling services quickly and precisely. This study aims to produce online counseling applications. The research method used is Research and development (R and D) which has ten stages of research. The development procedure consists of the pre-development stage to determine the need for cyber-based counseling service applications, the development stage is the activity of compiling product drafts, making applications, and application content, and the post-development stage is the trial stage to perfect the product, which is carried out by expert validators, practitioner validators and product trials by users. This research resulted in an online counseling application called the CarE application, namely Caring & Empathy Cyber ??Counseling which contains 10 service menus, namely classical guidance, orientation services, information services, group counseling, individual counseling, group counseling, peer counseling, case conferences, and reinforcement of instrumentation applications and system support.